Preliminary estimation of the novel coronavirus disease (COVID-19) cases in Iran: A modelling analysis based on overseas cases and air travel data. (May 2020) - Zhuang, Zian; Zhao, Shi; Lin, Qianying; Cao, Peihua; Lou, Yijun; Yang, Lin; He, Daihai
Highlights: As of March 1, 2020, Iran had reported 987 COVID-19 cases, including 54 associated deaths. At least six neighboring countries (Bahrain, Iraq, Kuwait, Oman, Afghanistan, and Pakistan) had reported imported COVID-19 cases from Iran. We estimated that 16 533 (95% confidence interval 5925–35 538) COVID-19 cases had occurred in Iran by February 25, 2020. Iran's ascertainment rate could have been at a level of 0.6% on February 25, 2020. Abstract: As of March 1, 2020, Iran had reported 987 novel coronavirus disease (COVID-19) cases, including 54 associated deaths. At least six neighboring countries (Bahrain, Iraq, Kuwait, Oman, Afghanistan, and Pakistan) had reported imported COVID-19 cases from Iran. In this study, air travel data and the numbers of cases from Iran imported into other Middle Eastern countries were used to estimate the number of COVID-19 cases in Iran. It was estimated that the total number of cases in Iran was 16 533 (95% confidence interval: 5925–35 538) by February 25, 2020, before the UAE and other Gulf Cooperation Council countries suspended inbound and outbound flights from Iran.